Improving Literacy Skills through The Storytelling Method for Early Childhood - Fono, Yasinta Maria; Sayangan, Yohanes Vianey; Gulo, Oktaviani (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
This research aims to describe the increase in literacy skills of young children through the storytelling method. PAUD schools were chosen as a means of cultivating literacy skills because it is hoped that by familiarizing themselves with literacy from an early age, children can improve their literacy skills as a preparation for facing the future. Literacy has a broad scope, not only talking about reading and writing letters, but also the ability to capture information with logical and critical thinking, ultimately being able to use it effectively to achieve certain goals. One method of increasing literacy in students is by using the storytelling method. This research is a qualitative research. Data collection techniques used by observation, interviews and documentation. Data analysis techniques used by data reduction, data presentation and data conclusions. The results of this research showed that the storytelling method could improve children's literacy skills and children not only enjoy the listening but children have the ability to tell stories.